The effect and cost-effectiveness of a group-based parenting intervention for parents of preschool children with subclinical neurodevelopmental disorders and mental health problems: protocol for a multiple-baseline single-case experimental design (SCED) with a pre-, post and follow-up - Anton Dahlberg; Vedrana Bolic Baric; Filipa Sampaio; Karin Fängström (BMC Psychology)
Abstract Background Young children with subclinical neurodevelopmental disorders (NDDs) and concurrent emotional and behavioral problems (EBP) are at significant risk of negative short- and long-term outcomes. Although early parenting support interventions are recommended and requested, there is a lack of interventions specifically designed for this group and adapted to the Swedish context. Based on this gap, a parenting support intervention for parents with children aged 2–6 years with subclinical NDDs and EBP has been co-created with clinicians and parents. The project described in this study protocol aims to evaluate the effectiveness and cost-effectiveness of this new group-based parenting intervention. Methods The project uses a multiple-baseline single-case experimental design (SCED) with pre-post measures and a 3-month follow-up. The intervention is provided to families with children who are referred to child health psychologists at the child pediatric outpatient clinic in Uppsala Region, Sweden. Outcomes will include child EBP and parent self-efficacy, stress, well-being, and quality of life, as well as costs for the intervention, health care use, and QALYs. Discussion The project could lead to improved mental health in both children and parents through participation in the group-based parenting intervention. The study design, with longitudinal data from both children and/or their parents, will provide valuable insights into the trajectories of mental health and well-being within this group. In addition, the inclusion of young children as informants will provide important information about their experiences. Furthermore, the use of pre-, post- and follow-up questionnaires will allow reliable and clinically significant changes to be assessed and our findings to be compared with randomized trials in similar populations. The results of this project will be relevant to children with subclinical NDDs and their parents, as well as to health care organizations and the scientific community. The intervention is well adapted to the end users and the clinical context, as it has been co-created with clinicians and parents. Trial registration ISRCTN10835479 https://doi.org/10.1186/ISRCTN10835479 , date of registration 2024-10-08.